Effects of lower extremity neuromuscular and mechanical characteristics on running economy and sports performance of long-distance runners under different relative paces - Tan, Zhengze; Li, Zihao; Ding, Yiling; Wang, Dantong; Wang, Yongan (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveTo explore the potential correlational patterns between lower extremity explosive power, strength balance, joint stiffness, neuromuscular characteristics and running economy (RE) as well as personal best (PB) of long-distance runners under different relative paces, so as to provide a preliminary theoretical clues for optimizing endurance training.MethodsTen male second-class long-distance runners were recruited. Under the paces of PB70%, PB80% and PB90%, RE, maximal oxygen uptake (VO2max), lower extremity explosive power (CMJ, SJ, EUR, RSI), joint peak torque ratio (PTR), joint stiffness and neuromuscular indicators (RMS, CAR) were tested using gas metabolism analysis, force platform, isokinetic strength testing system, motion capture system and electromyography equipment. Data were processed by one-way repeated measures analysis of variance, paired samples t-test and Pearson correlation analysis.ResultsRE increased significantly with the increase of pace (p < 0.05), and the correlation between RE and PB at PB80% and PB90% was stronger than that between VO2max and PB; RSI was significantly negatively correlated with RE70%, RE90% and PB (p < 0.05), while CMJ, SJ and EUR had no significant correlation; at 180°/s angular velocity, the hip joint flexor eccentric-extensor concentric PTR was significantly positively correlated with RE70%, RE90% and PB, and the knee joint flexor concentric-extensor eccentric PTR was significantly positively correlated with RE at all paces and PB (p < 0.05); knee joint stiffness was significantly negatively correlated with RE at all paces (p < 0.05); the RMS of vastus medialis (VM) was significantly positively correlated with RE70% and RE90%, and the knee joint CAR was significantly negatively correlated with RE at all paces (p < 0.05).ConclusionThis study is strictly exploratory and hypothesis-generating. RE is a core indicator potentially associated with long-distance running performance. RSI, specific hip and knee PTR at 180°/s angular velocity, knee joint stiffness and knee joint neuromuscular activation characteristics (VM RMS, knee joint CAR) show potential correlational associations with RE. The associations between these indicators and RE are pace-dependent and joint-specific, which can provide preliminary scientific reference for generating hypotheses about long-distance running training.